Factors Motivating the Decision to Major in Mathematics at the Higher Secondary Level - Badaila, B. B.; Dhakal, B. P. (Pragya Darshan प्रज्ञा दर्शन, 2024)
This study focuses on the “Motivational Factors for Choosing Mathematics as a Major Subject at Higher Secondary Level.” The objectives of this study were to explore the motivational factors of students choosing mathematics as a major subject and to explore the strategies of students majoring mathematics at higher secondary level. It is case study and qualitative in nature. One mathematics teacher and twelve students (six boys and six girls’) were respondents of the study which were selected through purposive sampling. Interview and Classroom observation was used as data collection tools during teaching learning activities. The collected information was analyzed with the help of theoretical and conceptual framework. The finding of the study shows that, the majority of students believe that mathematics is an easy subject from their childhood and that they are all proficient at it, obtaining a decent profession in the future is conceivable. Despite this, it is also seen that, there are not enough math students; this is because society does not place a high importance on math education. The number of mathematics students will raise if we introduce the new trend of thinking among students that mathematics is not a tough subject, it is an interesting one.